The prophylactic effect of aqueous chamomile extract on sulfur dioxide exposed mice - Kbaysi, Maryam; Petrosyan, Ruzanna; Borjac, Jamilah (Edelweiss Applied Science and Technology, 2025)
Sulfur Dioxide (SO2) is an atmospheric contaminant known for its harmful effects on various organs. Chamomile, traditionally used for several years, has shown efficacy in treating and alleviating various disorders due to its antioxidant properties. This study aims to examine the prophylactic effect of Chamomile extract on mice exposed to sulfur dioxide. Four groups of Balb/c mice (n=9 per group) were used. Group 1 received no treatment (control); Group 2 was given Chamomile extract orally at 200 mg/kg body weight for 14 days; Group 3 was exposed to SO2 (sodium sulfite and sodium bisulfite, 3:1 ratio) via intraperitoneal injection at 690 mg/kg for 7 days; Group 4 received Chamomile for 7 days before co-administration with SO2 for an additional 7 days. After treatment, blood was collected and the liver, brain, and lungs were harvested for histological and biochemical analyses. SO2 exposure elevated liver enzymes and malondialdehyde levels, reduced SOD and CAT activity, and caused lung histological damage without brain alterations. Chamomile extract significantly alleviated these effects. Chamomile shows preventive effects against SO2-induced damage, supporting its use as a protective agent against environmental contaminants.